HXD2F AC Drive Heavy-haul Freight Electric Locomotive - Haiping WANG; Shiyong LYU; Hua LI (机车电传动)
The main technical parameters and characteristics of HXD2F AC drive heavy axle load freight electric locomotive were introduced. The main performances and characteristics of electric control system, traction system, braking system and mechanical system of the locomotive were described. The main technical innovation points of the locomotive were described. The application appraisal and disassembly check showed that HXD2F AC drive heavy axle load freight electric locomotive has excellent overall performance for heavy haul traction.